Effects of a process-oriented goal setting model on swimmer's performance - Simoes, P.; Vasconcelos-Raposo, J.; Silva, A.; Fernandes, H. M. (Journal of Human Kinetics, 2012)
The aim of this work was to study the impact of the implementation of a mental training program on swimmers' chronometric performance, with national and international Portuguese swimmers, based on the goal setting model proposed by Vasconcelos-Raposo (2001). This longitudinal study comprised a sample of nine swimmers (four male and five female) aged between fourteen and twenty, with five to eleven years of competitive experience. All swimmers were submitted to an evaluation system during two years. The first season involved the implementation of the goal setting model, and the second season was only evaluation, totaling seven assessments over the two years. The main results showed a significant improvement in chronometric performance during psychological intervention, followed by a reduction in swimmers' performance in the second season, when there was no interference from the investigators (follow-up).